Design Construction of Patchouli Oil Direct Steam - Octo Fandi Sinaga; Lukman Adlin Harahap; Adian Rindang (Universitas Sumatera Utara, 2016)
Distillation is one of the ways to take up patchouli oil that contained in the leaves, the example is leaf clovers. Leaf clovers has the high oil content with euganol that reaches of 85%. The postharvest processing’s purpose is to make the agricultural product have a higher economic value compared to the product without processed. The purpose of this research was to design, build, test and analyze the economic value of patchouli oil direct steam distillation type. The parameters observed were effective capacity and economic analysis. Based on this research, it were summarized that the effective capacity of the equipment was 13,33 ml/hour. Economic analysis, basic costs for the first to the fifth year was Rp. 1.054,77/ml, Rp. 880,48/ml, Rp. 822,67/ml, Rp. 793,82/ml and Rp. 776,55/ml. Break even point (BEP) for the first to the fifth year was 247,17 ml/year, 133,02 ml/year, 95,16 ml/year, 76,27 ml/year and 64,95 ml/year. Net present value (NPV) 6% was Rp. 12.060.105 whereas NPV 8% was Rp. 10.793.704,29 and Internal rate of return this equipment was 27,04%. Keywords : leaf clovers, distillation, machine